Easily missed: Acute rotator cuff tears - Craig, R; Holt, T; Rees, J (BMJ Publishing Group, 2017)
A 45-year-old woman falls on ice and injures her shoulder. Assessment at her local hospital reveals bruising only and no bony injury on plain radiographs. Despite ongoing reassurance and participation in a physiotherapy programme for three months, she continues to complain of pain, weakness and inability to raise her arm. Eventually she is referred to a specialist shoulder clinic where an ultrasound scan confirms she suffered an acute full thickness tear of her supraspinatus tendon.